Ephemera : a memoir - Loewinsohn, Briana (Fantagraphics Books, Inc., 2023)
Ephemera is a poetic and dreamlike take on a graphic memoir set in a garden, a forest, and a greenhouse. The story drifts among a grown woman, her early memories as a child, and the gossamer existence of her mother. A lyrical entry in the field of graphic medicine, Ephemera is a story about a daughter trying to relate to a parent who struggles with mental illness. Gorgeously illustrated in a painted palette of warm, earthy tones, it is a quiet book of isolation, plants, confusion, acceptance, and the fog of childhood. Loewinsohn's debut book is an aching, meditative twist on autobiography, infusing the genre with an ethereal fusion of memory and imagination. Full-color illustrations throughout.